About Archive Policies: Questions for Discussion - Stegmayer, María (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The article aims to review and discuss some of the issues related to the link between archive, democracy and State in the book Anarchivismo. Political Technologies of the Archive, by Andrés Maximiliano Tello (La Cebra, 2018) with the objective of outlining a series of questions from which the question of archive policies or better, of the nature of the links between arcontic power, capitalist machine and anarchist subversion, as proposed in the book, can be approached taking into account some singular edges of the processes of social democratization that occurred in the recent history of some Latin American countries and in which the State played a fundamental role.
Keywords: Archive; State; Police